2011
DOI: 10.1098/rspb.2011.1376
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetic basis of animal domestication

Abstract: Genomic technologies for livestock and companion animal species have revolutionized the study of animal domestication, allowing an increasingly detailed description of the genetic changes accompanying domestication and breed development. This review describes important recent results derived from the application of population and quantitative genetic approaches to the study of genetic changes in the major domesticated species. These include findings of regions of the genome that show between-breed differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 85 publications
2
85
1
1
Order By: Relevance
“…In particular, the average allelic and genetic diversity found in our work exceeds that reported for a caprine gene pool from the geographic center of goat domestication in Iran and Pakistan (Di et al, 2011;Vahidi et al, 2014). This result was unexpected because genetic diversity, for most livestock species, tends to be negatively correlated with geographic distance from the center of domestication (Groeneveld et al, 2010;Wiener and Wilkinson, 2011). Pereira et al (2009) reported high maternal (mtDNA) and paternal (Y-chromosome) genetic diversity among goat populations from Northern Africa.…”
Section: Allelic and Genetic Diversitycontrasting
confidence: 55%
“…In particular, the average allelic and genetic diversity found in our work exceeds that reported for a caprine gene pool from the geographic center of goat domestication in Iran and Pakistan (Di et al, 2011;Vahidi et al, 2014). This result was unexpected because genetic diversity, for most livestock species, tends to be negatively correlated with geographic distance from the center of domestication (Groeneveld et al, 2010;Wiener and Wilkinson, 2011). Pereira et al (2009) reported high maternal (mtDNA) and paternal (Y-chromosome) genetic diversity among goat populations from Northern Africa.…”
Section: Allelic and Genetic Diversitycontrasting
confidence: 55%
“…Comparing with the wild camel, we found that an overall lower heterozygosity rate exists in the exon regions but not in other parts of the domestic camel genome, suggesting an artificial selection for certain genes in the domestic species30. As strong artificial selection would reduce genetic diversity around a locus (selective sweep)31, it was worth inspecting the genes and their functions in such a locus. We therefore used 10-kb windows to scan the genome to identify regions where the heterozygosity rate of the domestic camel is significantly lower than the wild one ( P <0.05 after Bonferroni correction, χ 2 -test) (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…As a result, many beneficial alleles were fixed or nearly fixed in specificl breeds as genetic changes occurred in population differentiation accompanying the domestication preocess28. In our study, the 54-bp insertion allele frequencies in the ancestor, indigenous and modern chickens displayed significant population differentiation.…”
Section: Discussionmentioning
confidence: 58%